Determination of urinary sulfatides and other lipids by combination of reversed-phase and thin-layer chromatographies - Berná, L; Asfaw, B; Conzelmann, E; Cerný, B; Ledvinová, J (Analytical biochemistry, 1999)
A fast and simple method for determination of sulfatides in the urine of patients with metachromatic leukodystrophy (MLD, arylsulfatase A deficiency) has been developed. The procedure consists of two steps: extraction of total urinary lipids by reversed-phase chromatography and their HPTLC separation. Two types of sorbents based on different matrixes were compared, of which the hydroxyethyl methacrylate C-18 type sorbent was found to be superior. Twenty-milliliter aliquots of urine are sufficient for the analysis. The technique is appropriate for simultaneous qualitative identification and semiquantitative densitometric determination and is suitable for routine work. The amount of sulfatides is expressed in relation to sphingomyelin, which copurifies with sulfatides and better reflects the level of membrane lipids in urine than commonly used parameters (creatinine, urine volume, etc.). The ranges were found to be 0.15-0.68 nmol sulfatide/nmol sphingomyelin for control individuals and 3.5-27.2 nmol sulfatide/nmol sphingomyelin for MLD patients. The excretion of sulfatides is pathonognomic for true MLD (due to the accumulation in kidney) and therefore its analysis is important for evaluation of suspected MLD cases including clinically and enzymatically atypical cases. The method is also useful as a complementary analysis for other lipidoses with high excretion of sphingolipids in urine (e.g., Fabry disease).
Keywords: Fabryho nemoc; Fabry Disease; chromatografie na tenké vrstvě; metachromatická leukodystrofie; Leukodystrophy, Metachromatic; Proteinuria; Lipids; chromatografie; lipidy; proteinurie; lidé; Case-Control Studies; studie případů a kontrol; Chromatography, Thin Layer; Humans; sulfoglykosfingolipidy; Chromatography; Sulfoglycosphingolipids